1978
DOI: 10.1021/bi00606a033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substituents on the rates of deacylation of substituted benzoyl papains. Role of a carboxylate residue in the catalytic mechanism

Abstract: The effect of ring substituents on the rates of deacylation of 8 meta- and para-substituted benzoyl papains was evaluated. The rate constants were found to depend upon a single ionizing group of pKa = 4.2--4.3, and to decrease by a factor of approximately 2.2 when measured in 94% D2O/H2O. The rates of deacylation are increased greatly by electron-withdrawing groups on the benzene ring. The Hammett rho value is 2.74 +/- 0.32. A plot of the rate constants for deacylation of the benzoyl papains against the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

1980
1980
1992
1992

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
(65 reference statements)
2
11
0
Order By: Relevance
“…Thus it is apparent from the sigmoidal pH dependence of deacylation that the basic form of a group with PKa approx. 4 is required for catalytic activity (Whitaker & Bender, 1965;Williams & Whitaker, 1967;Lowe, 1976;Zannis & Kirsch, 1978). This type of pH-dependence has been interpreted, in common with the serine proteinases, in terms of general base catalysis (Fersht, 1977).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Thus it is apparent from the sigmoidal pH dependence of deacylation that the basic form of a group with PKa approx. 4 is required for catalytic activity (Whitaker & Bender, 1965;Williams & Whitaker, 1967;Lowe, 1976;Zannis & Kirsch, 1978). This type of pH-dependence has been interpreted, in common with the serine proteinases, in terms of general base catalysis (Fersht, 1977).…”
Section: Discussionmentioning
confidence: 96%
“…Such rotation is implied by the observation of acid catalysis of amide substrate hydrolysis (Lowe & Yuthavong, 1971), cryoenzymological studies (Angelides & Fink, 1978), active site thiol group modification studies (Brocklehurst & Malthouse, 1978;Brocklehurst et al, 1979a,b), and consideration of stereoelectronic constraints (Deslongschamps et al, 1975). Evidence for the involvement of Asp-158 in the catalytic mechanism has come from recent work on pH-rate profiles (Allen et al, 1978) and structure-reactivity correlations (Zannis & Kirsch, 1978). Consequently a charge relay system in papain is an intriguing possibility; it cannot be ruled out a priori.…”
mentioning
confidence: 99%
“…The validity of this assumption was questioned (Husain & Lowe, 1968) and was practically ruled out by the determination of the steric structure of the enzyme, which showed that the nearest carboxyl group, which belongs to aspartate-158, was at a distance of 0.75 nm from the sulphur atom of cysteine-25 (Drenth et al, 1970(Drenth et al, , 1976. Based on the magnitude of the Hammett p value for the rates of deacylation of substituted benzoyl-papains, Zannis & Kirsch (1978) claimed that it was most likely that the deacylation of nonspecific acyl-enzymes is catalysed by a carboxylate group as a general base. Referring to these data, Angelides & Fink (1979b) raised the possibility that deacylation of specific substrates could also be assisted by aspartate-158.…”
Section: Role Ofaspartate-158 In Catalysismentioning
confidence: 99%
“…They concluded that the direct involvement of an uncharged histidine residue in the deacylation step in papain-catalysed reactions cannot be excluded. Johnson et al (1981 b) have also pointed out that the near-zero heat of ionization of the catalytic group of pKa = 4, another argument in favour of carboxylate participation (Zannis & Kirsch, 1978), is not inconsistent with the action of imidazole as a general base.…”
Section: Role Ofaspartate-158 In Catalysismentioning
confidence: 99%
See 1 more Smart Citation